2019
DOI: 10.1002/adfm.201902929
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurized Polyacrylonitrile Cathodes with High Compatibility in Both Ether and Carbonate Electrolytes for Ultrastable Lithium–Sulfur Batteries

Abstract: Sulfurized polyacrylonitrile (SPAN) is a promising material capable of suppressing polysulfide dissolution in lithium-sulfur (Li-S) batteries with carbonate electrolyte. However, undesirable spontaneous formation of soluble polysulfides may arise in the ether electrolyte, and the conversion of sulfur in SPAN during the lithiation/delithiation processes is yet to be understood. Here, a highly reliable Li-S system using a freestanding fibrous SPAN cathode, as well as the sulfur conversion mechanism involved, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
206
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(217 citation statements)
references
References 53 publications
11
206
0
Order By: Relevance
“…This disadvantage can be addressed by additives. Liu et al showed the PAN fibers with an appropriate amount of CNTs can still be self-standing after sulfurization [115]. The sulfur only exists in the form of Li 2 S 2 and Li 2 S 3 rather than polysulfides in the sulfurized PAN.…”
Section: Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…This disadvantage can be addressed by additives. Liu et al showed the PAN fibers with an appropriate amount of CNTs can still be self-standing after sulfurization [115]. The sulfur only exists in the form of Li 2 S 2 and Li 2 S 3 rather than polysulfides in the sulfurized PAN.…”
Section: Electrospinningmentioning
confidence: 99%
“…d Inorganic particles encapsulated carbon fibers [114]. e The modification of carbon fibers [115]. f Carbon fiber membrane with nanoparticles [38].…”
Section: Vacuum Filtrationmentioning
confidence: 99%
“…[25] Sulfur undergoes as ingle-electron process, which yielded atheoretical capacity of 837 mAh g À1 .The extra capacity originated from the conjugative structure when combined with the reaction pathway.A lthough both of conclusions self-consistently illustrated the source of extra capacity,t he p-conjugated pyridinic carbon matrix cannot afford such high capacity. [19,21,26] Wang et al revealed that the lithiation process of S@pPAN is as ingle-phase solid-solid route with the sole discharge product being Li 2 S. [27] The irreversible capacity of Li with C = Nb onds during the initial discharge process would lead to exceeding capacity and enhance ionic conductivity.T hey further confirmed that the control step of the rate capacity is the activation process of Li 2 S. Recently,Xie et al introduced small amount of selenium (Se) to alter the structure of S@pPAN composite. [28] It delivered excellent performance,b oth in ester and ether electrolytes.Based on the above analysis,weassume that the molecular structure of the S@pPAN composite should be highly dependent on the precursor PA N, the synthesis temperature,t ime,a nd pressure.…”
Section: Structure Of the S@ppan Compositementioning
confidence: 99%
“…In comparison with liquid electrolyte Li batteries, solid-state batteries have lower power densities. This is the result of limited kinetics of the electrodes, the compatibility of the electrode/electrolyte interface, and the solid electrolyte low ionic conductivity [72]. Recently, the development of high ionic-conductive solid electrolytes has made the production of solid-state Li batteries possible with a power performance similar to liquid-electrolyte batteries.…”
Section: Batteries With Solid Electrolytementioning
confidence: 99%